Peppa and the new baby - Holowaty , Lauren (London Ladybird Books, 2023)
What happened when Peppa met her baby brother George for the first time? In this brand new story, Peppa remembers meeting her baby brother George for the first time! Tiny Peppa learns what babies can and can't do, and finds out what it means to be a big sister. This heartwarming story will be loved by all fans of Peppa Pig, especially those who are getting ready to welcome a new sibling"--Publisher's description
English stories
Keywords: Animal fiction; Picture books